2007
DOI: 10.1111/j.1365-2788.2007.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation in the 2005 general election by adults with intellectual disabilities

Abstract: The importance of the close proximity of an active voter is likely to be different for adults in supported accommodation compared with those living in private households. Further research is required to understand what features of these two very different types of residences are affecting voting opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 3 publications
3
31
0
2
Order By: Relevance
“…A study from the UK has confirmed the belief that people with learning disabilities are under-represented at the polls. 7 The study also found that adults with learning disabilities were six times more likely to vote if they lived with at least one other adult who voted-a finding that agrees with Norwegian research. 8 In the United States, research shows that although many people with mild to moderate dementia vote, they are more likely to do so if their carer is a spouse rather than a son or daughter.…”
supporting
confidence: 82%
“…A study from the UK has confirmed the belief that people with learning disabilities are under-represented at the polls. 7 The study also found that adults with learning disabilities were six times more likely to vote if they lived with at least one other adult who voted-a finding that agrees with Norwegian research. 8 In the United States, research shows that although many people with mild to moderate dementia vote, they are more likely to do so if their carer is a spouse rather than a son or daughter.…”
supporting
confidence: 82%
“…People with ID were less likely to participate in decision making (including voting) and were less likely to take part in their local community. This report is in keeping with other UK research Emerson 2007;Keeley et al 2008).…”
Section: Introductionsupporting
confidence: 87%
“…This report is in keeping with other UK research (Emerson et al . 2005; Emerson 2007; Keeley et al . 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The practical and social barriers to voting for people with cognitive impairments are discussed by Keeley et al (2007) and Kohn (2008).…”
Section: Notesmentioning
confidence: 99%